Tourism untuk Kampong Melayu Laut: Solusi Digital dalam Pengelolaan Data Pengunjung dan Promosi Terintegrasi - Ariffin, Muchammad; Andrey Indra Maulana, Uray; Faisal, Muhammad; Pratiwi, Windi; Zaskia Meica, Dayang; Ronaldo, Fransiskus (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The Community Partnership Empowerment Program (PKM) in Kampong Melayu Laut Tourism Village, Pontianak City, was implemented to address key challenges in tourism management, namely the lack of visitor data systems and limited digital promotion strategies. The program adopted a smart tourism approach through the development of the website www.wisatakampongmelayu.com and digital marketing training for local tourism groups (Pokdarwis). The implementation stages included socialization, training, technology application, mentoring, and evaluation. The results showed significant improvement in participants’ understanding of digital data management by 18% and digital marketing skills by 32.5%. The developed website functions as a digital platform for visitor data recording, tourism promotion, and community-based information sharing. The program’s impact includes increased social media engagement, active community participation in tourism promotion, and improved accessibility of visitor analytics. Thus, the integration of digital technology has proven effective in enhancing community capacity, strengthening destination branding, and supporting sustainable tourism development. This initiative serves as a replicable model for digital tourism village development in West Kalimantan and across Indonesia.